Experimental and histological study of reparative osteogenesis in conditions of different methods of fixation during allograft alocompositive arthroplasty of long bones - Vyrva, Oleg; Golovina, Yanina; Malyk, Roman; Danishchuk, Zinayda; Nikolchenko, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The study of bone regeneration in the case of application of allocomposite endoprosthetics is an important area of research in orthopedics. Objective: to study the regeneration processes using allocomposite endoprosthetics to replace postresection segmental defects of the femur with various fixation methods in rats. Methods: models of various variants of fixing the allograft to the bone of the recipient have been developed and improved; a model of cementless fixation of an endoprosthesis with ceramic stem coating using an allograft has been proposed. The experiment was carried out on 45 laboratory white rat cells (age 5 months, body weight 350–400 g), which were divided into three groups of 15 each: I — transverse osteotomy of the femur with implantation of the allocomposite endoprosthesis; II — transverse osteotomy of the femur with implantation of the allocomposite endoprosthesis and autoplasty of junctional zone between bone and allograft; III — stepped osteotomy with implantation of the allocomposite endoprosthesis. The animals were sacrificed at 3, 6 and 9 months, and histological examination was performed. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Results:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> after transverse osteotomy of the femur (group I and II) and substitution of postresection defects of the proximal part with allocomposite endoprostheses, allografts were reorganized at all terms of the study. Symptoms of inflammation are not established in any case. With the increase in the contact plane of the allograft with the recipient bone (step osteotomy, group III), the processes of reorganization and vascularization of the allograft were more pronounced. Signs of active reorganization of autografts were observed from the 3<span style="font-size: 14.0pt; mso-bidi-font-size: 5.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; font-style: normal; mso-bidi-font-style: italic;">rd<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">month of the experiment. Bone fusion of an autograft with a bone of the recipient is established after 9 months after operation. On the perimeter of the endoprosthesis, the newly formed bone tissue was in tight contact with the ceramic coating of the endoprosthesis.